Pathology and first report of natural eye infection with the trematode Philophthalmus gralli (Digenea, Philophthalmidae) in Tinamus major (Tinamiformes, Tinamidae), Costa Rica - Rojas Araya, Diana (2013)
The eye-fluke Philophthalmus gralli (Philophthalmidae Looss, 1899) was found in six birds known as great tinamous (Tinamusmajor) reared in awild animal shelter located in Alajuela, Costa Rica. The birds presented conjunctival hyperemia, blepharitis, anorexia and weakness. Some of them suffered from unilateral blindness and ocular loss. After morphometric analysis, the specimens showed characteristics compatible with the digenean trematode P. gralli. The clinical signs of infection were resolved by manual removal of the adults, treatment with praziquantel and relocation into an environment without a natural water source. In order to determine if an ongoing cycle of this pathogen was present in the shelter, the habitat of the birds was inspected for the presence of infected intermediate hosts and contaminated water and objects. It was found that the snails Melanoides tuberculata acted as the intermediate host, and reared the infectious stages toward other animals, as shown by the reproduction of ocular philophthalmiasis in chickens artificially infected with excysted metacercaria. Moreover, three out of every ten snails found in the place were infected with rediae of P. gralli, raising the possibility of the dispersion of the parasite into new environments as well as the imminent zoonotic risk. The finding of P. gralli in Costa Rica is the first official report in Central America.